2015
DOI: 10.5812/ijhrba.21945
|View full text |Cite
|
Sign up to set email alerts
|

Prescription Drugs, Alcohol, and Illicit Substance Use and Their Correlations Among Medical Sciences Students in Iran

Abstract: Background:Substance use among young people is a major public health problem in Iran.Objectives:The aims of the present study were to determine the prevalence of substance misuse and its determinants in medical sciences students in Tehran, Iran.Patients and Methods:A cross-sectional study was performed on a randomly selected sample of 1992 medical sciences students during 2012-2013. Anonymous, structured questionnaires were distributed among the students in each selected class. Substance misuse was defined acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
67
4
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(88 citation statements)
references
References 22 publications
16
67
4
1
Order By: Relevance
“…The highest prevalence of simulant use was reported by Barati et al in a study among university students in Hamadan; the prevalence of lifetime use of methamphetamine, ecstasy and LSD were 18%, 8.5% and 4.8% respectively (15). However, in 3 other studies that reported methamphetamine and/or amphetamine use, the prevalence of lifetime use was less than 1% in the total sample (16)(17)(18). Two studies reported the prevalence of lifetime use by sex: 0.8 and 1.6% in boys, and 0.1 and 0.6% in girls (16,18).…”
Section: University Studentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The highest prevalence of simulant use was reported by Barati et al in a study among university students in Hamadan; the prevalence of lifetime use of methamphetamine, ecstasy and LSD were 18%, 8.5% and 4.8% respectively (15). However, in 3 other studies that reported methamphetamine and/or amphetamine use, the prevalence of lifetime use was less than 1% in the total sample (16)(17)(18). Two studies reported the prevalence of lifetime use by sex: 0.8 and 1.6% in boys, and 0.1 and 0.6% in girls (16,18).…”
Section: University Studentsmentioning
confidence: 99%
“…However, in 3 other studies that reported methamphetamine and/or amphetamine use, the prevalence of lifetime use was less than 1% in the total sample (16)(17)(18). Two studies reported the prevalence of lifetime use by sex: 0.8 and 1.6% in boys, and 0.1 and 0.6% in girls (16,18). The prevalence of use in the previous year was reported to be 0.2% and 1.1% in 2 studies (18,19).…”
Section: University Studentsmentioning
confidence: 99%
“…Their findings emphasize on planning preventive interventions by considering high-risk behaviors (22). In order to explain their relationship, Dyrbye and colleagues believed that burnout seems to be common among US medical students and may be increased as students proceed in their course.…”
Section: Discussionmentioning
confidence: 99%
“…Data from United States revealed that more than 60% of American college students reported past month alcohol use and 14.5% of the students reported past 30-day use of marijuana (24,25). Studies revealed that 2.6% to 7.6% and 8% to 17% of university students in Iran abused drugs and used alcohol at least once in the past 30 days (5,7,8,12,13). In the present study, 5.5% of the students had ever used alcohol and 2.4% had alcohol consumption in the past 30 days, and only 2.4% had an experience of drug abuse.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of occasionally and regular hookah smoking among university students in Iran was about 14% and 6%, respectively (10,11). Studies revealed that 2.6% to 7.6% and 8% to 17% of university students in Iran abused drugs and used alcohol at least once in the past 30 days (5,7,8,12,13).…”
Section: Introductionmentioning
confidence: 99%